FishBase 96 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
FishBase 96 is the second release of the CD-ROM database which contains data of more than 14,000 species of fish (seeSpore 59 p 10). The biological information offered for education and research purposes on all aspects of finfish is undercontinuous...